Microbiological criteria of cooked rice at point of sale from food services in the northern sector of the University of the Philippines-Diliman campus - Silva, Fralyn B. (College of Home Economics, University of the Philippines Diliman, 2013)
The microbiological criteria for boiled rice sampled at point of sale from food services in the northern sector of the University of the Philippines (UP) Diliman Campus was established based on microbial results generated. The four sampling sites used as sources of boiled rice samples were: Cooperative Convenience Store; College Canteen; University Cooperative Canteen; and Residential Canteen. Boiled rice sampled at point of sale in the northern sector of the University had pH of 5.70 to 6.53 and Aw of 0.879 to 0.918. The following microbiological profile were established: APC of 1.0 x 10^5 cfu/g & YMC of 1.0 x 10^4 cfu/g as utility indicators; CC of 30.0 MPN/g as the microbial quality indicator and; presumptive B. cereus counts of 1.0 x 10^4 cfu/g as the pathogenic indicator. The ICMSF (2002) scheme was employed to set values of the sampling plan parameters: n=5 & c=1 for APC, YMC & CC and n=10 & c=1 for B. cereus, based on stringency using a 3-class sampling plan. The microbial limits established in the study as defined by the parameters m (acceptable number of bacteria/g) & M (the number of bacteria/g above which a food borne outbreak may occur) to be followed were: APC (m= 10^5 cfu/g & M=10^8 cfu/g); YMC (m= 10^4 cfu/g & M=10^7 cfu/g); CC (m= 30.0 MPN/g & M=300.0 MPN/g) and; for B. cereus (m= 10^4 cfu/g & M=10^5 cfu/g). It was recommended that the microbial results generated in the study be validated to make more stringent microbial limits for boiled rice at point of sale within the UP Diliman Campus.